Correlation between the Knowledge Level of Pregnant Women about Prevention of Emergency Pregnancy and the Frequency of ANC Visits during the Covid-19 Pandemic at UPT Puskesmas Linggang Bigung - Farida Agustini; Joko Sapto Pramono; Nilam Noorma (Formosa Journal of Science and Technology, 2023)
This study aims to determine the relationship between the level of knowledge of pregnant women about emergency prevention of pregnancy and the frequency of ANC visits during the Covid 19 pandemic. This type of research is a correlational descriptive study with a cross-sectional research design. The population in this study were all third trimester pregnant women who were recorded in the working area of ​​the UPT Linggang Bigung Health Center in the July and December 2021 periods of 196 people. The sampling technique used was purposive sampling with a total sample of 30 people. The data analysis technique uses the Spearman rho test. Based on the research results obtained, it can be concluded that there is a relationship between the level of knowledge of pregnant women about prevention of emergency pregnancies and the frequency of ANC visits during the Covid 19 pandemic (p-value = 0.008).